Performance of cone beam computed tomography and conventional intraoral radiographs in detecting interproximal alveolar bone lesions: a study in pig mandibles - Vanessa Camillo Almeida; Lucas Rodrigues Pinheiro; Fernanda Cristina Sales Salineiro; Fausto Medeiros Mendes; João Batista César Neto; Marcelo Gusmão Paraíso Cavalcanti; Cláudio Mendes Pannuti (BMC, 2017)
Abstract Background Cone beam computed tomography (CBCT) has been largely used in dentistry. Nevertheless, there is lack of evidence regarding CBCT accuracy in the diagnosis of early periodontal lesions as well as the correlation between accuracy and lesion size. The aim of this study was to evaluate accuracy of CBCT and conventional intraoral radiographs in detecting different-sized interproximal bone lesions created in pig mandibles. The hypothesis was that CBCT accuracy would be superior to radiographs in detecting incipient bone lesions. Methods Twenty swine dry mandibles were used, totalizing 80 experimental sites. Four groups were created according to exposure time to perchloric acid 70-72%: controls (no exposure), 2-hour exposure, 4-hour exposure, and 6-hour exposure. Standardized CBCT and conventional intraoral radiographs were taken and analyzed by two trained radiologists. The presence of lesions in the dry mandible was considered the gold standard. Sensitivity, specificity, and accuracy in detecting different-sized bone lesions were calculated for CBCT and intraoral radiographs. Results Accuracy of CBCT ranged from 0.762 to 0.825 and accuracy of periapical radiography ranged from 0.700 to 0.813, according to examiner and time of acid exposure. Inter-examiner agreement varied from slight to fair, whereas intra-examiner agreement varied from moderate to substantial. Conclusions CBCT performance was not superior to that provided by conventional intraoral radiographs in the detection of interproximal bone loss.